EMPLOYEE SATISFACTION AT SURVEYAT UPTD PALARAN PUBLIC HEALTH CENTER IN SAMARINDA - Hasmariadi, Hasmariadi; Wirapuspita Wisnuwardani, Ratih (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Job satisfaction reflects the degree to which a person enjoys his or her job. Employee job satisfaction can be described as an employee's emotional state that occurs or does not occur at the intersection between the employee's job reward value and the company or organization the reward value that employees desire and achieve. Objective : This research aimed to determine employee satisfaction at Palaran Public Health in Samarinda City in order to improve the quality of services to patients. Research Methods/ Implementation Methods : This research used cross-sectional study, survey in July 2023 with 96 participants (23 males and 73 female) collected data on participant characteristics and employee satisfaction. Results : The data were provided as means of diplomas/D3, with 48% and 32% possessing college degrees, respectively. Most respondents (48%) had a work span of 10-20 years. In terms of employee status, 52% of respondents were ASN employees, while 34% were Honorary employees, with the majority of respondents working as nurses (27%), midwives (23%), and a huge number of workers. Leadership of 77.73, management of 76.50, Service Performance of 76.69, Organization Programs 75.91 and Personality 76.56. The results show that there is no relationship between employee satisfaction with level education p=0,893, employed status = 0,594, years of service p=0,393 and profession p=0,449. Conclusion/Lesson Learned : That employee satisfaction at the Public Health Center Palaran is satisfied indeed, though there are several factors that need to improve be involved in planning program.